2011
DOI: 10.1021/nl202728j
|View full text |Cite
|
Sign up to set email alerts
|

Directing Substrate Morphology via Self-Assembly: Ligand-Mediated Scission of Gallium–Indium Microspheres to the Nanoscale

Abstract: We have developed a facile method for the construction of liquid-phase eutectic gallium-indium (EGaIn) alloy nanoparticles. Particle formation is directed by molecular self-assembly and assisted by sonication. As the bulk liquid alloy is ultrasonically dispersed, fast thiolate self-assembly at the EGaIn interface protects the material against oxidation. The choice of self-assembled monolayer ligand directs the ultimate size reduction in the material; strongly interacting molecules induce surface strain and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
299
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(304 citation statements)
references
References 71 publications
5
299
0
Order By: Relevance
“…It is possible to form nanoparticles by sonicating liquid metal in ethanol 21 or 2-propanol. 22 However, simply sonicating liquid metal in water leads to an unstable suspension.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to form nanoparticles by sonicating liquid metal in ethanol 21 or 2-propanol. 22 However, simply sonicating liquid metal in water leads to an unstable suspension.…”
Section: Introductionmentioning
confidence: 99%
“…LMs such as gallium, gallium-indium eutectic alloys (EGaIn: 75% Ga, 25% In (wt wt −1 )), and gallium-indium-tin alloys (Galinstan: 68.5% Ga, 21.5% In and 10% Sn (wt wt −1 )), with melting points of 29.8, 15.7 and 10.7 °C, respectively, have received increasing attention because they are generally chemically stable and do not react with water at room temperature. In addition, previous studies have shown that such alloys are safe for humans under normal circumstances345678910. Currently, there is a significant interest towards the chemical345 and morphological characterization of these emerging LMs56789.…”
mentioning
confidence: 99%
“…As demonstrated by Hohman et al, 67 stable ethanolic nanoscale liquid-metal colloids can be produced using sonication, which induces mechanical separation to form liquid-metal nano-droplets due to the presence of high oscillating shear forces (Figure 3). Via this approach, the properties of the base solvent are exploited for processing and the self-healing (coalescing) properties of gallium-indium droplets for patterning.…”
Section: Ink-jet Printingmentioning
confidence: 96%